(untitled) (Khairulummah, 2024)
The question of Sufism’s origin and roots in Islam is a complex and much-debated issue. Since the latter half of the nineteenth century, scholars have presented conflicting perspectives on this matter. Earlier Orientalists typically viewed Sufism as stemming from a single external source, while more recent perspectives suggest it may have multiple roots. Nevertheless, both groups agree on one key point-that Sufism was a later addition to Islam and not an original part of it. Various perspectives have been put forward to explain its true origins, attributing it to influences from Persian, Indian, Christian, Jewish, or Neo-Platonic traditions. The present paper aims to challenge these view points and to demonstrate that Islamic Sufism finds its true roots directly in the Qur’anic revelation, the Sunnah of the Prophet, and the lives of his righteous companions.